Contratos de trabalho atípicos: da flexibilidade à informalização - Rosario, Carolina Goulart Moura (2021)
The object of this study is the atypical employment contracts built over the last four decades regarding the labor regulation aiming more flexibility and adaptation for the workforce to the new demands of the capitalist market. These agreements are the temporary work contracts, for a steady term and part-time regime, as a result of the influence of the neo-liberalizing winds in Brazil and the outsourced, intermittent and telecommuting work contract, consequences of the labor reform in 2017. The objective of this research is to understand the reflexes of transformations in the world of work and capitalism in the ways in which labor is contracted, identifying approach informality and the process of social precariousness in work. Thus, we started from the analysis of the formation process of the Brazilian market in order to understand the profile of work in the country. Then we investigate the impacts of productive restructuring and neo-liberal hegemony on labor laws in Brazil and the ways of hiring, presenting the six atypical contractual modalities and reflecting on the negative impacts on the working class. Finally, we identify the existing similarities among informality and these atypical contracts, starting from the concept of informal work by Maria Augusta Tavares, addressing the main conceptual discussions about informality, in order to determine its relationship with the social precariousness process of work. Through bibliographic research and documentary analysis on the laws that constitute or modify contracting modalities, we found out that, in the face of the instrumental rationality of capitalism, forms of work were introduced. These forms of work weaken the formal work relationship so much that they often assume the informal aspect. Therefore, we identified that new forms of work with atypical contracts have similarities with informal work, which enables us to understand them as participants in the social precariousness of work in progress, which implies an unprecedented process in the country and establishes an institutionalization of flexibility and precariousness, renewing the historical and structural precariousness of work in Brazil economically, socially and politically.